2019
DOI: 10.1155/2019/9846312
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of the Proinflammatory IL-6-JAK/STAT Signalling Pathways Responsible for Vascular Restenosis in Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes mellitus (T2DM) is increasing worldwide, and it is associated with increased risk of coronary artery disease (CAD). For T2DM patients, the main surgical intervention for CAD is autologous saphenous vein grafting. However, T2DM patients have increased risk of saphenous vein graft failure (SVGF). While the mechanisms underlying increased risk of vascular disease in T2DM are not fully understood, hyperglycaemia, insulin resistance, and hyperinsulinaemia have been shown to contribute to microvascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 123 publications
(165 reference statements)
2
43
0
2
Order By: Relevance
“…These analyses revealed that pre‐operative IL‐6 and IL‐8 expressions were independent risk factors for restenosis, and they disclosed predicting values for restenosis risk with AUCs more than 0.6; more importantly, when combining IL‐6, IL‐8, hypercholesteremia, diabetes mellitus, and HsCRP, the AUC for predicting restenosis risk was more than 0.9. The possible reasons for the results might be as follows: IL‐6 and IL‐8 were able to deteriorate disease conditions of CAD patients underwent PCI with DES via multiple effects (such as increased endothelial cell expression of adhesion molecules, activated the macrophages, increased metalloprotease expressions, and mediated the detrimental effects of angiotensin II to the vessels); therefore, the higher pre‐operative expressions of IL‐6 and IL‐8 predicted the increased risk of restenosis in CAD patients underwent PCI with DES …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These analyses revealed that pre‐operative IL‐6 and IL‐8 expressions were independent risk factors for restenosis, and they disclosed predicting values for restenosis risk with AUCs more than 0.6; more importantly, when combining IL‐6, IL‐8, hypercholesteremia, diabetes mellitus, and HsCRP, the AUC for predicting restenosis risk was more than 0.9. The possible reasons for the results might be as follows: IL‐6 and IL‐8 were able to deteriorate disease conditions of CAD patients underwent PCI with DES via multiple effects (such as increased endothelial cell expression of adhesion molecules, activated the macrophages, increased metalloprotease expressions, and mediated the detrimental effects of angiotensin II to the vessels); therefore, the higher pre‐operative expressions of IL‐6 and IL‐8 predicted the increased risk of restenosis in CAD patients underwent PCI with DES …”
Section: Discussionmentioning
confidence: 99%
“…The possible reasons for the results might be as follows: IL-6 and IL-8 were able to deteriorate disease conditions of CAD patients underwent PCI with DES via multiple effects (such as increased endothelial cell expression of adhesion molecules, activated the macrophages, increased metalloprotease expressions, and mediated the detrimental effects of angiotensin II to the vessels); therefore, the higher pre-operative expressions of IL-6 and IL-8 predicted the increased risk of restenosis in CAD patients underwent PCI with DES. 2,26,27 Rapid angiographic stenotic progression is another common complication in CAD patients underwent PCI with DES, which strikingly affects the treatment efficacy of PCI with DES. 7,28 Therefore, it is also crucial to investigate the biomarkers for predicting RASP risk.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the other cytokine trends indicate possible reversible action as variable expression patterns are viewed across time points. IP-10 and MIP-1b have known interactions and roles with the JAK/STAT protein pathway [24,25]. The JAK/STAT canonical pathway is a system of linked interactions involved in the phosphorylation of tyrosine residues in receptors creating active binding sites for proteins with Src-Homology (SH2) domains.…”
Section: Secreted Molecules Role In Signalling Pathways Controlling Nmentioning
confidence: 99%
“…e Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway plays a vital role in mediating angiogenesis against ischemic injury [11][12][13][14][15][16][17]. Importantly, JAK2/STAT3 signaling has been specifically shown to protect against cerebral ischemia-reperfusion injury by inducing microvessel proliferation [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%